2014
DOI: 10.1161/circep.114.001729
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Navigation of Left and Right Ventricular Leads to Optimal Targets for Cardiac Resynchronization Therapy

Abstract: Background-Left ventricular (LV) and right ventricular pacing site characteristics have been shown to influence response to cardiac resynchronization therapy (CRT). This study aimed to determine the clinical feasibility of image-guided lead delivery using a 3-dimensional navigational model displaying both LV and right ventricular (RV) pacing targets. Serial echocardiographic measures of clinical response and procedural metrics were evaluated. Methods and Results-Thirty-one consecutive patients underwent preimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…We previously demonstrated that CMR-derived scar and dyssynchrony can guide LV lead implantation 18 with excellent CRT response if pacing in a CMR target in keeping with the present findings. Similarly, Laksman et al 19 used CMR-derived scar and dyssynchrony-guided lead placement with echocardiographic super-response in 58% of patients. Currently there are limited clinical data describing the use of cardiac CT LV lead guidance.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that CMR-derived scar and dyssynchrony can guide LV lead implantation 18 with excellent CRT response if pacing in a CMR target in keeping with the present findings. Similarly, Laksman et al 19 used CMR-derived scar and dyssynchrony-guided lead placement with echocardiographic super-response in 58% of patients. Currently there are limited clinical data describing the use of cardiac CT LV lead guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal location for the RV lead tip was assigned first followed by the preferential LV pacing site. At follow-up, 74% of patients met the predefined echocardiographic criteria of a responder despite the fact that lead implantation was informed purely by fluoroscopy and visual assessment of the 3D models, and real-time guidance was used [137]. …”
Section: Multi-modality Imaging and Image Fusion Technologymentioning
confidence: 99%
“…LV regional function was estimated in accordance with the 17-Segment American Heart Association (AHA) model. 24 The apical segments (ie, segments [13][14][15][16][17] and the septal segments (ie, segments 2, 3, 8, and 9) were not considered as possible targets for lead placement, 4,25 and therefore were not included in the model. Following the procedure outlined by the STARTER 11 trial, strain curves were analyzed for the remaining 8 free wall segments imaged using short-axis views at mitral valve and papillary muscle level.…”
Section: Imagingmentioning
confidence: 99%
“…Cardiac resynchronization therapy implantation is performed under X‐ray guidance which provides an excellent visualization of catheters and pacing leads but lacks detailed information on cardiac function and structure. Studies have demonstrated that multimodality image fusion could be used to overcome these limitations. However, they rely on techniques and imaging modalities which are not part of the clinical routine for CRT candidates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation